Study of sleep habits and their effective factors in children admitted to Amirkabir Hospital, Arak - Fahimeh Omidi; Mona Hamedi Tabar; Parsa Yousefi chaijan; Hamed Kakekhani (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2023)
Introduction: Sleep disorders are the most common behavioral complaints in children. Therefore, this study was conducted to determine the sleep habits of children admitted to Amirkabir Hospital, Arak, Iran. Material & Methods: In this descriptive cross-sectional study, children aged 4 to 12 years admitted to Amirkabir Hospital clinic in 2021 were randomly studied. Data obtained from the Children's Sleep Habits Questionnaire were analyzed using SPSS24.0 software. Findings: A total of 295 children with a mean age of 7.26±2.27 years were studied. The prevalence of the disorder in sleep habits was 67.4%. Among the children with disturbed sleep habits, 193 (96.9%) had poor sleep habits and 6 (3.1%) had average sleep habits. The total sleep habits score was significantly higher in girls, unwanted children, and children with divorced parents, low parental education level, and incompatible parents (P<0.05). However, there was no significant association between the total sleep habits score and children's age (P>0.05). Discussion & Conclusion: In this study, most children showed disturbed sleep habits. Considering that children's poor sleep habits may be a contributing factor for stress, pressure, and tension in the family, mass education and psychiatric intervention are needed in this regard.